Differences in Efficiency and Effectiveness of Micro Waqf Banks In Indonesia Before and During The Covid-19 Pandemic - Heriyanti, Chrisna; Asmuni; Sumitra, Andri (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
he decline in economic activity induced by covid-19 affects the financial and social efficiency of microfinance institutions (MFIs). This study aims to analyze the efficiency and effectiveness of Micro Waqf Banks before and during the covid-19 pandemic. The sample of this research is Micro Waqf Banks located throughout Indonesia that have complete data to be obtained using Data Envelopent Analysis (DEA). The findings of this study are that in 2018 the efficient Micro Waqf Banks were 25 units or around 78% which were effective there were 22 units or around 93% the average efficiency value was 95%, while the average effectiveness value was 81%. In 2019, there were 29 efficient Micro Waqf Bank units or around 58%, of which there were 19 effective units or around 37% with an average efficiency value of 87%, while the average effectiveness value was 78%. In 2020, efficient Micro Waqf Banks increased to 41 units or around 82%, effective ones increased from 2019 to 22 units, with an average efficiency value of 93% with an average effectiveness value of 77%.